2008
DOI: 10.1088/0953-8984/21/2/026007
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic studies of multiferroic Bi1−xSmxFeO3ceramics synthesized by mechanical activation assisted processes

Abstract: Bi(1-x)Sm(x)FeO(3) (x = 0.0-0.2) ceramic samples were prepared by mechanical activation assisted solid-state-reaction synthesis. A stoichiometric mixture of Bi(2)O(3), Sm(2)O(3), and Fe(2)O(3) powders was mechanically milled and this was followed by heat treatment at 700 °C for 1 h. Room temperature x-ray diffraction patterns confirmed the formation of perovskite structured Bi(1-x)Sm(x)FeO(3) phase. Vibrating sample magnetometry measurements showed that to a certain extent, Sm doping of BiFeO(3) leads to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 36 publications
5
42
0
2
Order By: Relevance
“…It is expected that the EB in these system originate from the exchange interaction at the interfaces of weakly ferromagnetic and antiferromagnetic components [48]. The asymmetry in the M-H curve was also observed at RT with 10 % Sm doping in a similar type of ceramics Bi 1−x Sm x FeO 3 [49]. The authors reported that in this compound while most of the sample remain largely antiferromagnetic, regions in the Sm-doped BiFeO 3 sample become weakly ferromagnetic and their interaction results an asymmetric behaviour in the M-H curve although the effect was not observed for 20 % Sm doping.…”
Section: +mentioning
confidence: 66%
“…It is expected that the EB in these system originate from the exchange interaction at the interfaces of weakly ferromagnetic and antiferromagnetic components [48]. The asymmetry in the M-H curve was also observed at RT with 10 % Sm doping in a similar type of ceramics Bi 1−x Sm x FeO 3 [49]. The authors reported that in this compound while most of the sample remain largely antiferromagnetic, regions in the Sm-doped BiFeO 3 sample become weakly ferromagnetic and their interaction results an asymmetric behaviour in the M-H curve although the effect was not observed for 20 % Sm doping.…”
Section: +mentioning
confidence: 66%
“…The saturation magnetization ( ), , and values were found to be 1.36 emu/g, 0.05 emu/g, and 4.71 Oe, respectively. A weak ferromagnetic behaviour was observed for BLFO and BDFO sample due to the suppression of space modulated spin structure [28,29]. Doping by La at Bi site in BFO leads to distortion in rhombohedral structure.…”
Section: Magnetic Hysteresis Analysismentioning
confidence: 94%
“…In spite of this complex magnetic behavior, this compound has a great potential for information storage, sensors, and electric field controlled devices. It has been shown that by substitution of elements at the A-site (Bi) or B-site (Fe), the SSMS can be suppressed and, therefore, enhancement of the magnetic properties is evidenced [6][7][8][9][10][11][12][13][14][15]. Rare-earth elements (La, Nd, Eu, Dy, Gd, Ho, Y, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Rare-earth elements (La, Nd, Eu, Dy, Gd, Ho, Y, etc.) can be substituted at the A-site and, thus, improve ferroelectric and magnetic properties [7,8,[12][13][14][15]. Guo et al [15] reported that Gd doped BiFeO 3 nanoparticles synthesized via sol-gel method increase remnant magnetization with the increase of the Gd substitution.…”
Section: Introductionmentioning
confidence: 99%